Assessment of Nigerian Newspapers’ Reportage of Violence against Children: Case Study of Daily Sun and Punch National Newspapers - Nkwam-Uwaoma, Adeline .O.; Ndukwu, Mishack (Advances in Social Sciences Research Journal, 2021)
Traditionally, child rearing in Nigeria closely reflects the “spare the rod and spoil the child” maxim and as such spanking, flogging, slapping, beating and evening starving a child as a form of punishment for wrong doing and as a method of behavior modification are common. These are not necessarily considered as maltreatment or abuse of the child. Despite the adoption and implementation of the Child Rights Act in Nigeria, violence against children seems to be on a steady increase. Stories of sexual molestation, rape, child labour, infliction of physical injuries and use of children for rituals by parents, guardians and other members of the society abound. Violence against children is considered as those acts by other persons especially adults that undermine and threaten the healthy life and existence of children or those that violet their rights as humans. In Nigeria newspapers are a major source of News, second only to radio and television in coverage, currency and content. National dailies are newspapers with daily publications and national spread or coverage. This study analyzed the frequency, length, prominence level, direction and sources of information reported on violence against children in the selected national daily newspapers. It then provided information on the role of the newspapers in Nigeria in the fight against child violence and public awareness of the impact of violence against children on development of the nation and the attempts to curtail such violence. The composite week sampling technique in which the four weeks of the month are reduced to one and a sample is randomly selected from each day of the week was used. As such 168 editions of Daily Sun and Punch newspapers published from January to December of 2016 were selected. Data were collected using code sheet and analyzed via content analysis. The result showed that the frequency of the newspapers’ reportage of violence against children in Nigeria was low. Again, it was found that the length or space given to reports on violence against children was inadequate, the direction of the few reports on violence against children was in favor of the course or fight against child violence and these newspapers gave no prominence to reports on violence against children. Finally, it was found that major source of news about violence against children was through journalism; government and individual sources provided only minimal information. Adeline Nkwam-Uwaoma and Mishack Ndukwu Keywords – children, Newspapers Reportage, Nigeria, Violence Nkwam-Uwaoma is with the Department of Mass Communication , Imo State University, P.M.B. 200 Owerri , Nigeria (corresponding author, phone +2348035414973; email: nkwamuwaomaadline@yahoo.com ) Ndukwu is with Imo State University, P.M.B. 2020 Owerri, Nigeria (email: mishack.cj@gmail.com ).